Antiqua et Nova and Shifting Religious Authority: The Catholic Church’s Response to Artificial Intelligence through a Postmodernist Paradigm - Dinata, Arfi Pandu; Kuswana, Dadang (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This study explores the intersection between artificial intelligence (AI) and religious authority through a critical analysis of Antiqua et Nova, an official document issued by the Dicastery for the Doctrine of the Faith and the Dicastery for Culture and Education of the Catholic Church. The document is examined as a theological and ethical response to the challenges posed by the rapid advancement of AI, particularly its influence on spiritual practices and the potential shift in symbolic authority within religious life. Employing a qualitative content analysis method, this research focuses on how the Catholic Church addresses the tension between technological innovation and the preservation of human dignity, moral responsibility, and spiritual authenticity. The discussion is situated within the framework of postmodern thought, which emphasizes the decentralization of truth claims, the rise of digital mediation, and the erosion of traditional epistemic hierarchies. In this context, Antiqua et Nova offers a cautious yet constructive approach: it neither rejects AI outright nor embraces it uncritically. Instead, it affirms the importance of ethical discernment, the primacy of human relationality, and the irreplaceability of embodied spiritual presence. This article concludes that the Catholic Church, through Antiqua et Nova, seeks to maintain the integrity of religious authority by articulating a theological framework that critically engages with AI while upholding the foundational principles of Christian anthropology and moral theology.